Barriers in Using English Movies: Enhancing Students’ Listening Skills - Al Anwar, Sylvia Febbryani; Arjulayana; Nargis (Institut Agama Islam Negeri Palopo, 2025)
This study investigates the internal barriers faced by university students when using English movies to improve their listening skills. Conducted at the University of Muhammadiyah Tangerang, this research used a qualitative descriptive method involving 24 first-semester students through classroom observation and interviews. The results identified four main barriers: difficulty understanding grammar, limited vocabulary, dependency on subtitles, and trouble recognizing accents. For instance, many students struggled to follow figurative language and idiomatic expressions such as “get your head out of the clouds.” Others reported confusion when characters spoke too quickly or with unfamiliar pronunciation. These challenges limited students’ ability to fully comprehend the dialogue, despite their interest in using movies as a learning tool. The findings indicate that watching movies alone is not enough to improve listening skills without structured support. Therefore, educators should handle these barriers by providing guided activities such as teaching key vocabulary before viewing, using pause-and-reflect techniques, and conducting post-viewing discussions. These steps can help turn passive watching into an active learning process and enhance listening comprehension at the university level.